Bridging the Pedagogical Divide: Identifying Curricular Strengths and Gaps in Saudi Translation Studies Programs through Stakeholder Perceptions - Almutairi, Fawziah Faez (Advances in Social Sciences Research Journal, 2026)
The aim of this research is to examine the strengths and weaknesses of Translation Studies programs in Saudi Arabia from the graduates' and employers' perspectives. The research focuses specifically on curriculum alignment and graduates' employability. The research is informed by the competence-based model of translation, Constructive Alignment theory, and employability concepts. An explanatory sequential mixed-methods research design is used for this research. Quantitative research is carried out using structured questionnaires from 100 graduates and 50 employers. The research instruments aim to measure graduates' and employers' perceptions of graduates' linguistic competence, cultural competence, technological competence, and project management competence. Statistical analysis techniques used for quantitative research include descriptive statistics, independent samples t-test, ANOVA, effect size statistics (Cohen's d and Eta squared), and post-hoc tests using Tukey's method. The research findings show that graduates performed well in linguistic and cultural competence areas. There are no statistically significant differences between graduates and employers in these areas. However, graduates performed poorly in technological competence and project management competence areas. The research found significant gaps between graduates and employers' perceptions in these areas. ANOVA analysis showed substantial discrepancies between competency domains, which indicate structural imbalances in curriculum design. These results indicate a partial match between educational training and the requirements of the modern translation industry. The study concludes that, although the translation studies programs offered in Saudi Arabia have a good foundation in theory and bilingual training, they need to be integrated with training on using technology, artificial intelligence, and working with professionals to improve the employment prospects of graduates. The results of this study can be used as a set of recommendations for improving the curriculum of translation studies programs.